A comparison of information on motor vehicle crashes as reported by written or telephone interviews. Issue 2 (3rd April 2006) - Alonso, A; Laguna, S; Seguí-Gómez, M
Abstract : Objective: To compare information about traffic crash injuries and kilometers driven reported in a written questionnaire with information reported in a telephone interview. Design: Telephone and paper surveys. Setting: The Seguimiento Universidad de Navarra (SUN, University of Navarra Follow-up) study, in Spain. The SUN study is an open enrollment cohort study with 17 000 enrolled graduates followed through biennial mailed questionnaires. Subjects: A sample of 542 individuals from the SUN study participants. Main outcome measure: Agreement on information about traffic crash injuries and mileage driven in a mailed questionnaire and a telephone survey. Results: Participation was 90.4%. Considering the phone survey as the gold standard, data on traffic crash injuries in the mailed questionnaire had 83% sensitivity (95% CI 77% to 89%), 77% specificity (95% CI 71% to 82%), 74% positive predictive value (95% CI 67% to 80%), and 89% negative predictive value (95% CI 83% to 93%). Agreement beyond chance, measured by the kappa statistic, was 0.63 (95% CI 0.56 to 0.70). Correlation between questionnaire and telephone surveys and kilometers driven on average during a year assessed by the intraclass correlation coefficient was 0.64 (95% CI 0.57 to 0.70), p<0.001. Conclusions: Information on sustained traffic crash injuries and traveled mileage over the previous two years as reported through mailed questionnaires in a highly educated population could be used in the study of associations between traffic crash injuries and a variety of risk factors.